An efficient quasi solid state dye sensitized solar cell based on polyethylene glycol/graphene nanosheet gel electrolytes. Issue 115 (5th November 2015) - Nath, Bikash Chandra; Das, Dhaneswar; Kamrupi, Isha Ruhulla; Mohan, Kiran Jyoti; Ahmed, Gazi Ameen; Dolui, Swapan Kumar
Abstract : A poly(ethylene glycol)/graphene nanosheet quasi solid gel electrolyte was synthesized using an in situ polymerization technique for dye-sensitized solar cells (DSSCs). Abstract : A poly(ethylene glycol)/graphene nanosheet quasi solid gel electrolyte was synthesized using an in situ polymerization technique for dye-sensitized solar cells (DSSCs). Fabrication of the DSSCs was carried out by sandwiching the poly(ethylene glycol)/graphene nanosheet (PEG/graphene nanosheet) gel electrolyte in between the dye sensitized TiO2 nanoflower photoanode and platinum based counter electrode using a spacer of thickness 25 μm. However, the graphene nanosheets form a network with PEG matrix channels in the gel electrolyte which enhances charge transportation. The PEG/graphene nanosheet gel electrolyte was characterized using Fourier transform infrared spectroscopy, cyclic voltammetry, scanning electron microscopy, transmission electron microscopy, thermal gravimetric analysis, atomic force microscopy and electrochemical impedance spectroscopy. Electrochemical impedance spectroscopy results demonstrate the reduction of charge transfer resistance ( R ct ) with the incorporation of graphene nanosheets which promotes charge transportation through the gel electrolyte. The reduction of ( R ct ) enhances the device efficiency which was observed in the current density vs. voltage ( J – V ) measurements and thereby the incident photon to converted electron (IPCE) curves. The maximum photovoltaic conversion efficiency of 5.16% was achieved.